The victory with no name : the Native American defeat of the first American army - Calloway, Colin G. (Colin Gordon), 1953- (Oxford University Press, 2014)
"A balanced and readable account of the 1791 battle between St. Clair's US forces and an Indian coalition in the Ohio Valley, one of the most important and under-recognized events of its time"--